2008
DOI: 10.1002/ppul.20877
|View full text |Cite
|
Sign up to set email alerts
|

Can bronchodilator response predict bronchial response to methacholine in preschool coughers?

Abstract: The aim of the present study was to determine the relationship between bronchodilator response, assessed by interrupter resistance (Rint), and bronchial reactivity in preschool children with chronic cough. Thirty-eight children coughers (median age 5.0 years, range 2.8-6.4) were tested. Bronchodilator response was recorded within 4 months before methacholine challenge. Response to the latter was assessed using transcutaneous partial pressure of oxygen and Rint. Children were considered responders if a 20% fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Several studies have shown that BDR is associated with histamine or methacholine responsiveness in both children and adults with asthma [7][8][9]. Similarly, we found a significant, albeit weak, correlation between BDR and methacholine PC20.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Several studies have shown that BDR is associated with histamine or methacholine responsiveness in both children and adults with asthma [7][8][9]. Similarly, we found a significant, albeit weak, correlation between BDR and methacholine PC20.…”
Section: Discussionsupporting
confidence: 52%
“…It has been suggested that BDR is the physiological opposite of bronchoconstrictor responsiveness [6,9], and, therefore, that bronchial challenge tests can be replaced by bronchodilator tests in subjects with airway obstruction. Several studies have shown that BDR is associated with histamine or methacholine responsiveness in both children and adults with asthma [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study used spirometry to demonstrate airway reversibility in young children. The ability to measure a response to BDR was previously shown by nonspirometric techniques, including force oscillation, specific resistance measured in the plethysmograph [ 18 , 19 ], and the Rint technique [ 20 ]. It is not surprising, therefore, that spirometry could also identify response to BDR in our tested children.…”
Section: Discussionmentioning
confidence: 99%
“…Interrupter resistance (Rint) has the advantages of being relatively easily measured using commercially available, handheld equipment, and of an extensive knowledge base of normal values and variability in preschool children 11–15. Although baseline Rint (like baseline spirometry) is not sufficiently sensitive for reliable diagnosis of asthma,16 BDR measured by Rint is able to separate preschool children with asthma from normal controls with reasonably good sensitivity and specificity,17 18 and is correlated with methacholine responsiveness in preschool children with chronic cough 19. Rint has also been able to delineate a dose-response curve to salbutamol in preschool children similar to that using forced expiratory volume in 1 second (FEV 1 ) in older children 20.…”
Section: Introductionmentioning
confidence: 99%